If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 = x + 3x + 3 Reorder the terms: 15 = 3 + x + 3x Combine like terms: x + 3x = 4x 15 = 3 + 4x Solving 15 = 3 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 15 + -4x = 3 + 4x + -4x Combine like terms: 4x + -4x = 0 15 + -4x = 3 + 0 15 + -4x = 3 Add '-15' to each side of the equation. 15 + -15 + -4x = 3 + -15 Combine like terms: 15 + -15 = 0 0 + -4x = 3 + -15 -4x = 3 + -15 Combine like terms: 3 + -15 = -12 -4x = -12 Divide each side by '-4'. x = 3 Simplifying x = 3
| -5+2a=-13 | | 39=(x-4)*13 | | -6+4x^2= | | =21p+35q | | 3x+9=10+x | | 3(2y)-(y-1)=6 | | 8w+8=6w-4 | | 3/4x-6=9 | | 5/6x=90 | | 5/6x-90 | | X(x-5)=x^2+8x+11 | | p(x)=-10x^2+1760x-50000 | | 6xn=78 | | -0=-7+w | | 6k-23=-7(-7-2k) | | 4z-4=-7+z | | 147=-7d | | -6-2m=-0 | | 6x+2y+2x-5y=180 | | 5x+8=7y | | 14+x^3-2x=63 | | -30x-(2x)= | | 2(3k-1)=-6(3+9k) | | 6x+4=-3x-2 | | -(8y+3)-(-7y-8)=5 | | 8(3m+3)-2m= | | 3m-38=-7(m-6) | | -4+4x=0 | | x+-3y=15 | | 0=9x^2-62x-50 | | (13.5)(x)=42(10) | | -8x+15+10x+25=2 |